STUDENTS’ STRATEGIES IN LEARNING ENGLISH TENSES - Ni'mah, Risma Mualifatun (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
English as a language has its own structure. It is the basic thing must be learned to master English. In English, there is a sentence structure pattern called tense which deals with the way of constructing sentences based on time. Tenses have many patterns with different use. Besides, tenses also require many items, such as verb changing which is not required in Indonesian. This rule does not exist in Indonesia. Meanwhile, English is learned and taught in Indonesia as a subject in school. This becomes something complicated to be learned by Indonesian students. Some students feel confused when they have to learn about tenses. Some of them also consider that English is difficult because of tenses. Whereas, the students have to master tenses in order they can master English. However, actually there are some students who are successful in learning tenses. They use some strategies in learning tenses, so that they can master tenses well. Those strategies are not only useful for their understanding about tenses, but also useful for improving their English skills.